2009
DOI: 10.1007/s12262-009-0004-9
|View full text |Cite
|
Sign up to set email alerts
|

How good is compliance with surgical antibiotic prophylaxis guidelines in a tertiary care private hospital in India? A prospective study

Abstract: Purpose There is a need to study compliance with surgical antibiotic prophylaxis guidelines in India.Methods In this prospective study, 100 consecutive surgical procedures performed at a tertiary care private hospital in Mumbai, India were observed. The choice of antibiotic, timing and duration of administration were recorded and compared to the hospital guidelines.Results Appropriateness of choice of antibiotic was seen in 68%, timing in 89%, dose in 75% and duration in 63% of cases. Hundred percent complianc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
25
4
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 18 publications
(17 reference statements)
9
25
4
4
Order By: Relevance
“…Similar finding was found in study from Sudan (56.3%) [14]. There is false belief that broad/multiple antibiotics are more effective in preventing SSIs [15].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar finding was found in study from Sudan (56.3%) [14]. There is false belief that broad/multiple antibiotics are more effective in preventing SSIs [15].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, studies from different countries have found that SAP was used excessively and inappropriately [8][9][10][11][12][13][14][15][16][17][18][19]. A wide variation of overall compliance was seen that range from 0 to 71.9% in various surgical procedures, majority of these studies revealed that noncompliance were in terms of selection, timing of administration and prolonged duration of SAP; indication and dose of SAP were more satisfactory compliant than other parameters [20].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Asian countries have generally reported higher prevalence of inappropriate antibiotic use for prophylaxis (48-100%) when compared to developed countries (23.4%-55.2%) [15,16,17,18,19]. Inappropriate timing of antibiotic administration (36.4%) and inappropriate duration (34.5%) were found to be the main reasons for inappropriate prophylactic antibiotic which was also similar to previous studies [17,18,20]. The inappropriate timing of administration in our setting was most likely due to the lack of local institutional guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, despite the presence of evidence-based guidelines, poor adherence to guidelines has been reported internationally. [7][8][9][10][11][12][13] The King Hussein Cancer Centre (KHCC) in Amman, Jordan, is a 170-bed comprehensive teaching cancer centre with a surgical service consisting of nine teams with various specialties. Among these teams, an average of 25 patients are seen and five major elective surgeries are performed per day.…”
mentioning
confidence: 99%